Enhancing l-glutamine production in Corynebacterium glutamicum by rational metabolic engineering combined with a two-stage pH control strategy. (December 2021) - Lv, Qinglan; Hu, Mengkai; Tian, Lingzhi; Liu, Fei; Wang, Qing; Xu, Meijuan; Rao, Zhiming
Graphical abstract: Highlights: ARTP mutagenesis was applied for breeding strains. Sc GS with high catalytic efficiency was screened out. Overexpression of ppk promoted ATP regeneration. Two-stage pH control largely improved l -glutamine production. The maximum titer of l -glutamine reached 73.5 ± 3.1 g/L . Abstract: l -glutamine is a semi-essential amino acid widely used in the food and pharmaceutical industries. The microbial synthesis of l -glutamine is limited by lack of effective strains with high titer and safety. First, ARTP mutagenesis combined with high-throughput screening generated an l -glutamine-producing strain of Corynebacterium glutamicum with titer of 25.7 ± 2.7 g/L . Subsequently, a series of rational metabolic approaches were used to further improve l -glutamine production, which included increasing the carbon flow to l -glutamine ( proB and NCgl1221 knockout), enhancing the catalytic efficiency of the key enzyme ( glnE knockout and glnA screening and overexpression) and reinforcement of ATP regeneration ( ppk overexpression and RBS optimization). Finally, we proposed a two-stage pH control strategy to address the inconsistent effect of pH on cell growth and l -glutamine production. These combined strategies led to a 186.0% increase of l -glutamine titer compared to that of the initial strain, reaching 73.5 ± 3.1 g/L with a yield of 0.368 ± 0.034 g/g glucose.